PEMBERIAN BUAH PEPAYA PADA NY N KEHAMILAN TRIMESTER III DENGAN KONSTIPASI DESA KARANG ANYAR KECAMATAN LANGSA BARO KOTA LANGSA - Dewita, Dewita; Safitri, Fifi Widya; Hrp, Meliani Sukmadewi; Henniwati; Elizar, Elizar (Jurnal Ilmiah Kesehatan Ibu dan Anak, 2022)
Based on data from the World Health Organization (WHO), around 810 pregnant women die every day due to complications related to pregnancy and childbirth. The main complications that cause almost 75% of all maternal deaths in the world are bleeding, infection, preeclampsia and unsafe abortion. The care given to pregnant women in the third trimester was in accordance with normal pregnancy midwifery care. This care design used a case study design with a qualitative approach as the background of the third trimester normal pregnancy midwifery care for Mrs. N in Karang Anyar Village, Langsa Baro District, Langsa City from the first visit, second visit, and third visit. Data collection was carried out by interviewing pregnant women in the third trimester and the patient's family to obtain complete data with the format of normal pregnancy midwifery care. Midwifery care for normal pregnancy in the third trimester was provided starting from a physical examination which aimed to determine the health status of the client, counseling and giving papaya fruit which aimed to overcome constipation, providing education on pregnancy exercises to reduce back pain, as well as providing counseling on how to deal with frequent bowel movements at night. Midwifery care for normal pregnancy third trimester given to Mrs. N aged 24 years G1P0A0 with normal pregnancy.